2018
DOI: 10.1159/000487333
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy in Elderly Stroke Patients with Mild-to-Moderate Baseline Disability

Abstract: Background: The number of elderly patients suffering from ischemic stroke is rising. Randomized trials of mechanical thrombectomy (MT) generally exclude patients over the age of 80 years with baseline disability. The aim of this study was to understand the efficacy and safety of MT in elderly patients, many of whom may have baseline impairment. Methods: Between January 2015 and April 2017, 96 patients ≥80 years old who underwent MT for stroke were selected for a chart review. The data included baseline charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
3
29
2
1
Order By: Relevance
“…In the present series, patients with a prestroke mRS 1 had similar odds as patients with a prestroke mRS 0 of having a good outcome at 90 days while a prestroke mRS 2 was associated with poor functional outcome irrespective of age (multilevel OR: 0.31, 95% CI: 0.16–0.60, p = 0.001). Other authors have found a similar tendency of good outcomes at 90 days in patients with mild to moderate disability irrespective of age [22]. Nevertheless, even an mRS of 3 in elderly patients may allow them to live at home with some assistance, not needing nursing home care and thus reducing the need for rehabilitation and costs for society [23, 24].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present series, patients with a prestroke mRS 1 had similar odds as patients with a prestroke mRS 0 of having a good outcome at 90 days while a prestroke mRS 2 was associated with poor functional outcome irrespective of age (multilevel OR: 0.31, 95% CI: 0.16–0.60, p = 0.001). Other authors have found a similar tendency of good outcomes at 90 days in patients with mild to moderate disability irrespective of age [22]. Nevertheless, even an mRS of 3 in elderly patients may allow them to live at home with some assistance, not needing nursing home care and thus reducing the need for rehabilitation and costs for society [23, 24].…”
Section: Discussionmentioning
confidence: 81%
“…The mRS score was assigned as follows: 0, no symptoms; 1, no clinically relevant disability; 2, slight disability (able to look after own affairs without assistance but not to a full extent); 3, moderate disability (requires some help but able to walk unassisted); 4, moderately severe disability (unable to attend to own bodily needs or to walk without assistance); 5, severe disability (requires constant nursing care); and 6, dead. We defined stroke etiology according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) classification [22].…”
Section: Methodsmentioning
confidence: 99%
“…23 Similarly, others have shown that the mortality rate in patients greater than 80 treated with mechanical thrombectomy beyond 8 h of symptom onset was not significantly higher than patients treated within 8 h of symptom onset (56% versus 32.4%, p = 0.055); although not statistically significant, the mortality number was certainly higher among the group with an initial moderate disability compared to the group with mild disability. 33 Because of the small sample size, the lack of significance in mortality rates may be attributed to a statistical type-2 error, and additional studies are needed with a higher power to establish if mortality rates are significantly increased due to recanalization outside of 8 h from stroke onset.…”
Section: Delayed Reperfusion: Research/casesmentioning
confidence: 99%
“…8,[13][14][15][16][17][18][19][20][21][22][23][24][25] Older patients, however, have shown to have a suboptimal benefit from mechanical thrombectomy, often due to reduced recanalisation success secondary to tortuous atherosclerotic vasculature. 26,27 When looking at patients of a younger population, Mocco et al first brought together a study comprising seven patients under 35 years of age who all underwent endovascular stroke intervention. 28 Five out of seven regained independent function at time of discharge, whilst the remaining two were found to have regained functional independence by the time of follow-up at 25 months.…”
Section: Support For Thrombectomy In a Younger Childbearing Populationmentioning
confidence: 99%
“…Older patients, however, have shown to have a suboptimal benefit from mechanical thrombectomy, often due to reduced recanalisation success secondary to tortuous atherosclerotic vasculature. 26,27…”
Section: Support For Thrombectomy In a Younger Childbearing Populationmentioning
confidence: 99%